A composite solid electrolyte membrane and its preparation method and application
By using a combination of polymer matrix and halide film with excellent toughness and strength in an all-solid state battery, a dense film with low porosity is solved, and the problem of poor mechanical strength of the polymer electrolyte membrane is improved, and the safety and charging of the battery are improved. Discharge performance.
Patent Information
- Application Number
- CN202210863614.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-21
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-07-21
AI Technical Summary
The existing polymer electrolyte membranes have poor safety and charge and discharge performance of all-solid state batteries due to poor mechanical strength.
A polymer matrix with excellent toughness, elasticity and strength is used as a supporting structure, and a laminated polymer film and halide film are provided on its surface to form a dense film with low porosity to inhibit the growth of lithium dendrites and promote lithium ions. fast transmission.
It improves the toughness, elasticity, strength and thermal stability of the composite solid electrolyte membrane, and improves the safety and charge and discharge performance of solid-state batteries.
Smart Images

Figure BDA0003757664720000101 
Figure BDA0003757664720000111
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite solid electrolyte membrane and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density, low self-discharge rate, wide operating temperature, long cycle life, environmental friendliness, and no memory effect, so they have developed rapidly in the past decade. Currently, lithium-ion batteries use organic liquid electrolytes and special additives to increase battery voltage and achieve high energy density, but this may cause serious safety problems. With the development of new energy power battery technology, traditional liquid batteries have become increasingly unable to meet the needs of consumers, and lithium battery technology is developing towards the requirements of high safety and high energy density. The emergence of all-solid-state lithium-ion batteries (ASSLBs) has accelerated the development of large-scale energy storage systems such as electric vehicles and power grids. Therefore, the development of all-solid-state lithium-ion batteries with high energy density and high safety has become the future development trend of the industry.
[0003] As a new type of battery energy storage technology, the key technology of all-solid-state lithium-ion batteries lies in the solid electrolytes (SSEs) that eliminate the flammable liquid organic electrolytes in the original lithium-ion batteries, and improve safety and volume energy density through more effective packaging. Although a large number of studies have proposed the application of fast ion-conducting solids such as sulfides, oxides and phosphates in solid-state batteries, these batteries show shortcomings such as poor mechanical properties and low energy density cycles. With the deepening of all-solid-state lithium-ion battery research, polymer electrolytes have gradually become a new favorite in research and development. Although polymers are easy to prepare into thin films, the film strength is low, and the polymer electrolyte is prone to electrochemical and mechanical degradation interface problems with the positive electrode material. In addition, the polymer electrolyte membrane is easily pierced by lithium dendrites during the battery cell cycle, and is not resistant to high temperatures. When the voltage exceeds 4V in a high temperature environment, the polymer electrolyte microscopic groups are easily oxidized, resulting in reduced activity. For this reason, the existing technology mostly uses a single method of adding plasticizers to improve the ionic conductivity of polymer electrolytes, but this will also reduce the mechanical properties of the membrane, making polymer electrolytes a safety hazard to all-solid-state batteries. In addition, the prior art also discloses some composite electrolyte membranes of polymers and inorganic substances, such as polymer-oxides, polymer-sulfides and other forms of composites, but they also face the disadvantage of poor membrane mechanical strength and cannot improve their application status in all-solid-state lithium-ion batteries. Therefore, it is very important to develop a new composite solid electrolyte membrane to improve the safety and charge and discharge performance of all-solid-state batteries. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is that the existing polymer electrolyte membrane has poor safety and charge and discharge performance of all-solid-state batteries due to the poor mechanical strength of the membrane, and further provides a composite solid-state electrolyte membrane to improve the electrochemical properties of the polymer electrolyte membrane at the lithium metal negative electrode, enhance the mechanical strength, thermal stability and electrochemical properties of the polymer electrolyte membrane, and ensure that the all-solid-state battery achieves high safety and high charge and discharge performance.
[0005] The present invention also provides a method for preparing the composite solid electrolyte membrane and a solid-state battery comprising the composite solid electrolyte membrane.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] In one aspect, the present invention provides a composite solid electrolyte membrane. According to an embodiment of the present invention, the composite solid electrolyte membrane comprises a polymer matrix and a solid electrolyte membrane disposed on the polymer matrix, wherein the solid electrolyte membrane comprises a polymer membrane and a halide membrane disposed in a stacked manner.
[0008] The composite solid electrolyte membrane provided by the present invention adopts a polymer matrix with excellent toughness, elasticity and strength as a supporting structure, and a solid electrolyte membrane is arranged on the surface of the polymer matrix to provide lithium ion conductivity, and the addition of the halide membrane can cooperate with the polymer matrix to form a dense membrane with low porosity, thereby inhibiting the growth of lithium dendrites and also facilitating the Li + The rapid transmission of the battery promotes the cycle rate of the battery in a high-temperature environment, so that the formed composite solid electrolyte membrane exhibits the advantages of good toughness, good elasticity, high strength, good thermal stability and high ion conductivity, which can improve the safety and charge and discharge performance of the solid-state battery.
[0009] In some embodiments of the present invention, the halide membrane is disposed adjacent to the polymer matrix, and the solid electrolyte membrane is disposed on one side of the polymer matrix; in other embodiments of the present invention, the solid electrolyte membrane may also be disposed on both sides of the polymer matrix.
[0010] In some embodiments of the present invention, the raw material composition of the polymer membrane includes a polymer electrolyte and a lithium salt, and the mass ratio of the polymer electrolyte to the lithium salt is 1 to 20: 1, preferably 1 to 5: 1. The addition of a proper proportion of lithium salt can improve the ionic conductivity of the composite solid electrolyte membrane.
[0011] Optionally, the polymer electrolyte is at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinyl alcohol, polycarbonate, polyacrylonitrile, polyvinyl pyrrolidone, polyethylene glycol, polyethylene oxide, and polymethyl methacrylate.
[0012] Preferably, the polymer electrolyte is polyethylene glycol and polyethylene oxide in a mass ratio of 1-2:1-3, thereby improving the film toughness of the polymer film and thus enhancing the film strength.
[0013] Optionally, the lithium salt is at least one of lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium trifluoromethylsulfonyl imide, lithium bis(oxalatoborate), lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium chloride, lithium hexafluorophosphate, and lithium perchlorate.
[0014] Optionally, the thickness of the polymer film is 2 to 50 μm, preferably 5 to 30 μm, thereby improving the toughness and strength of the polymer film.
[0015] In some embodiments of the present invention, the porosity of the polymer matrix is 30-80%, and the thickness is 2-40 μm, thereby improving the toughness, elasticity and strength of the composite solid electrolyte membrane.
[0016] Optionally, the polymer matrix is at least one of non-woven fabric, fiber membrane, melt-blown fabric, and porous membrane. Thus, the toughness, elasticity, and strength of the composite solid electrolyte membrane can be improved.
[0017] Optionally, the polymer matrix is made of at least one of polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyoxymethylene, polyamide, polycarbonate, polylactic acid, polymethyl methacrylate, acrylonitrile-styrene copolymer, polybutylene terephthalate, phenolic resin, and amino resin.
[0018] In some embodiments of the present invention, the thickness of the halide film is 5-40 μm, thereby improving the ion conductivity of the composite solid electrolyte membrane.
[0019] Optionally, the raw material of the halide film is at least one of Li3InCl6, Li3YbCl6, Li3YCl6, Li3ScCl6, and Li3GaCl6.
[0020] On the other hand, the present invention also provides a method for preparing the above composite solid electrolyte membrane, comprising the following steps:
[0021] Under a protective atmosphere, the polymer electrolyte, the lithium salt and an organic solvent are mixed to obtain a slurry, the slurry is coated into a film, and the film is dried in a protective atmosphere, and then vacuum dried to obtain the polymer film;
[0022] The polymer film, the raw material of the halide film, and the polymer matrix are stacked and pressed into a film.
[0023] In some embodiments of the present invention, the mass ratio of the polymer electrolyte to the organic solvent is 1:15-25, preferably 1:15-20.
[0024] Optionally, the organic solvent is at least one of methylformamide, acetonitrile, cyclohexanone, heptane, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0025] In some embodiments of the present invention, the drying temperature in the protective atmosphere is 20 to 30° C., and the drying time is 2 to 72 hours, preferably 4 to 24 hours.
[0026] Optionally, the vacuum drying temperature is 30 to 80° C., preferably 40 to 60° C., and the vacuum drying time is 4 to 72 h, preferably 12 h.
[0027] In some embodiments of the present invention, the pressing temperature is 30-150° C. and the pressure is 1-10 MPa.
[0028] On the other hand, the present invention further provides a solid-state battery, comprising the composite solid-state electrolyte membrane as claimed in claim 1 or a composite solid-state electrolyte membrane prepared by the method for preparing the composite solid-state electrolyte membrane as described above.
[0029] The solid-state battery provided by the present invention adopts a polymer matrix with excellent toughness, elasticity and strength as the supporting structure of the diaphragm, and a solid electrolyte membrane is arranged on the surface of the polymer matrix to provide lithium ion conductivity, and the addition of the halide membrane can cooperate with the polymer matrix to make the composite membrane form a dense membrane with low porosity, thereby inhibiting the growth of lithium dendrites, and also facilitating the Li + The rapid transmission of the battery promotes the cycle rate of the battery in a high-temperature environment, so that the formed composite solid electrolyte membrane exhibits the advantages of good toughness, good elasticity, high strength, good thermal stability and high ion conductivity, which can improve the safety and charge and discharge performance of the solid-state battery.
[0030] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0031] 1. The composite solid electrolyte membrane provided by the present invention comprises a polymer matrix and a solid electrolyte membrane arranged on the polymer matrix, wherein the solid electrolyte membrane comprises a polymer membrane and a halide membrane arranged in a stacked manner. The composite solid electrolyte membrane provided by the present invention adopts a polymer matrix with excellent toughness, elasticity and strength as a supporting structure, and a solid electrolyte membrane is arranged on the surface of the polymer matrix to provide lithium ion conductivity, and the addition of the halide membrane can cooperate with the polymer matrix to form a dense membrane with low porosity of the composite membrane, thereby inhibiting the growth of lithium dendrites, and also facilitating the Li +The rapid transmission of the battery promotes the cycle rate of the battery in a high-temperature environment, so that the formed composite solid electrolyte membrane exhibits the advantages of good toughness, good elasticity, high strength, good thermal stability and high ion conductivity, which can improve the safety and charge and discharge performance of the solid-state battery.
[0032] 2. The method for preparing the composite solid electrolyte membrane provided by the present invention is simple, fast, environmentally friendly, and suitable for large-scale production.
[0033] 3. The solid-state battery provided by the present invention adopts a polymer matrix with excellent toughness, elasticity and strength as the supporting structure of the diaphragm, and a solid electrolyte membrane is arranged on the surface of the polymer matrix to provide lithium ion conductivity. The addition of the halide membrane can cooperate with the polymer matrix to form a dense membrane with low porosity, thereby inhibiting the growth of lithium dendrites and also facilitating the Li + The rapid transmission of the battery promotes the cycle rate of the battery in a high-temperature environment, so that the formed composite solid electrolyte membrane exhibits the advantages of good toughness, good elasticity, high strength, good thermal stability and high ion conductivity, which can improve the safety and charge and discharge performance of the solid-state battery.
[0034] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0035] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0036] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0037] In one aspect, the present invention provides a composite solid electrolyte membrane. According to an embodiment of the present invention, the composite solid electrolyte membrane comprises a polymer matrix and a solid electrolyte membrane disposed on the polymer matrix, wherein the solid electrolyte membrane comprises a polymer membrane and a halide membrane disposed in a stacked manner.
[0038] According to an embodiment of the present invention, the composite solid electrolyte membrane provided by the present invention adopts a polymer matrix with excellent toughness, elasticity and strength as a supporting structure, and a solid electrolyte membrane is arranged on the surface of the polymer matrix to provide lithium ion conductivity, and the addition of the halide membrane can cooperate with the polymer matrix to form a dense membrane with low porosity, thereby inhibiting the growth of lithium dendrites, and also facilitating the Li + The rapid transmission of the battery promotes the cycle rate of the battery in a high-temperature environment, so that the formed composite solid electrolyte membrane exhibits the advantages of good toughness, good elasticity, high strength, good thermal stability and high ion conductivity, which can improve the safety and charge and discharge performance of the solid-state battery.
[0039] In some embodiments of the present invention, the halide film is arranged adjacent to the polymer matrix. On the one hand, the ionic conductivity of the composite solid electrolyte can be improved. On the other hand, since the elasticity of the inorganic halide film is not as good as that of the organic polymer film and the polymer matrix, the halide film is sandwiched between the polymer film and the polymer matrix. While ensuring that the halide and the polymer form a dense film, the inorganic layer can be protected by the organic flexible layer to prevent the halide film from breaking under high temperature or a certain mechanical strength, thereby affecting the battery interface stability.
[0040] According to actual needs, technicians in this field can choose to set the solid electrolyte membrane on one side or both sides of the polymer matrix. When the solid electrolyte membrane is set on both sides of the polymer matrix, the composite process is conducive to the solid electrolyte membrane to better fill or penetrate the gaps in the polymer matrix, so that the electrolyte distribution on both sides of the composite membrane is more uniform, which is conducive to the consistency of conductivity of various parts of the large-area composite membrane, thereby avoiding the formation of lithium dendrites and short circuits caused by local conductivity and uneven texture.
[0041] In some embodiments of the present invention, the raw material composition of the polymer membrane includes a polymer electrolyte and a lithium salt, and the mass ratio of the polymer electrolyte to the lithium salt is 1 to 20:1, preferably 1 to 5:1. Adding lithium salt can improve the ionic conductivity of the composite solid electrolyte membrane. The inventors found that if the mass ratio of the polymer electrolyte to the lithium salt is too high, that is, the proportion of lithium salt is small, it cannot provide good lithium ion transfer ability, resulting in low conductivity of the electrolyte membrane itself, and if the mass ratio of the polymer electrolyte to the lithium salt is too low, that is, the lithium salt is excessive, lithium salt will precipitate after the membrane is dried, resulting in a waste of resources and making it difficult to disperse the slurry.
[0042] Optionally, the polymer electrolyte is at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinyl alcohol, polycarbonate, polyacrylonitrile (PAN), polyvinyl pyrrolidone, polyethylene glycol (PEG), polyethylene oxide (PEO), and polymethyl methacrylate.
[0043] Preferably, the polymer electrolyte is polyethylene glycol and polyethylene oxide in a mass ratio of 1-2:1-3, thereby improving the film toughness of the polymer film and thus enhancing the film strength.
[0044] Optionally, the lithium salt is at least one of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium trifluoromethylsulfonyl imide, lithium bis(oxalatoborate) (LiBOB), lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium chloride, lithium hexafluorophosphate, and lithium perchlorate. Optionally, the thickness of the polymer film is 2 to 50 μm, preferably 5 to 30 μm. Thus, the toughness and strength of the polymer film can be improved.
[0045] In some embodiments of the present invention, the porosity of the polymer matrix is 30-80% and the thickness is 2-40 μm. Thus, the toughness, elasticity and strength of the composite solid electrolyte membrane can be improved. The inventors found that if the porosity is too low, it is not conducive to the passage of ions on both sides of the electrolyte membrane, and if the porosity is too high, the support strength of the matrix deteriorates and cannot effectively enhance the strength of the membrane; if the polymer matrix is too thin, the matrix itself is easily damaged under high temperature and high pressure, and the production cost of the too thin polymer matrix is high, and if the polymer matrix is too thick, the lithium ion channel path on both sides of the electrolyte membrane is too long, which is not conducive to the electrochemical performance.
[0046] Optionally, the polymer matrix is at least one of non-woven fabric, fiber membrane, melt-blown fabric, and porous membrane. Thus, the toughness, elasticity, and strength of the composite solid electrolyte membrane can be improved.
[0047] Optionally, the material of the polymer matrix is at least one of polyethylene (PE), polypropylene (PP), polystyrene, polyvinyl chloride, polyoxymethylene, polyamide, polycarbonate, polylactic acid (PLA), polymethyl methacrylate, acrylonitrile-styrene copolymer, polybutylene terephthalate, phenolic resin, and amino resin.
[0048] In some embodiments of the present invention, the thickness of the halide film is 5-40 μm, thereby improving the ion conductivity of the composite solid electrolyte membrane.
[0049] Optionally, the raw material of the halide film is at least one of Li3InCl6, Li3YbCl6, Li3YCl6, Li3ScCl6, and Li3GaCl6.
[0050] The inventors found that if the solid electrolyte membrane (i.e., the total thickness of the polymer membrane and the halide membrane) is too thin, it is difficult to prepare a composite electrolyte membrane that meets the basic requirements. If the solid electrolyte membrane is too thick, the composite electrolyte membrane will be thicker as a whole, the ion transfer path will increase, the battery impedance will increase, and the excessive mass will not be conducive to improving the battery energy density.
[0051] On the other hand, the present invention also provides a method for preparing the above composite solid electrolyte membrane, comprising the following steps:
[0052] S1. Under a protective atmosphere, the polymer electrolyte, the lithium salt and an organic solvent are mixed to obtain a slurry. The organic solvent can dissolve both the polymer electrolyte and the lithium salt. Optionally, the organic solvent is at least one of methylformamide, acetonitrile, cyclohexanone, heptane, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide. The mass ratio of the polymer electrolyte to the organic solvent is 1:15-25, preferably 1:15-20, so as to ensure both sufficient dissolution of the polymer electrolyte and the lithium salt and complete volatilization of the organic solvent.
[0053] S2, coating the slurry into a film, drying it in a protective atmosphere, and then vacuum drying it to obtain the polymer film. In this step, the slurry can be coated on the support material, and the polymer film can be obtained by separating the support material after drying. The specific type of the support material is not particularly limited, as long as the polymer film of the present application can be demolded after drying. For example, the support material can be a polytetrafluoroethylene plate or a release paper. In some embodiments of the present invention, the drying temperature in the protective atmosphere is 20 to 30 ° C, and the time is 2 to 72 hours, preferably 4 to 24 hours. Since lithium salts are easily hydrolyzed, and the temperature requirements for drying and dehydration are high, which will affect PEO, it is necessary to dry in a protective atmosphere to volatilize excess organic solvents, and then further vacuum heating and dehydration are performed to achieve the purpose of thorough drying. The temperature of the vacuum drying is 30 to 80 ° C, preferably 40 to 60 ° C, and the time of the vacuum drying is 4 to 72 hours, preferably 12 hours. The vacuum drying can be carried out at a vacuum degree of -0.1 to 10 MPa, so that the drying effect can be achieved without adversely affecting the polymer film.
[0054] S3, stacking the polymer film, the raw material of the halide film, and the polymer matrix and pressing them into a film at a certain temperature and pressure. In some embodiments of the present invention, the pressing temperature is 30-150° C. and the pressure is 1-10 MPa.
[0055] It should be noted that in the above preparation method, the mixing ratio of the polymer electrolyte and the lithium salt and the types of their respective substances, the thickness of the polymer film, the thickness, porosity and type of the polymer matrix, and the thickness and type of the halide film are the same as those described above and will not be repeated here. Since the lithium salt is easily hydrolyzed when it comes into contact with water, it is necessary to operate under a protective atmosphere, and the protective gas can be an inert gas such as nitrogen and argon.
[0056] On the other hand, the present invention further provides a solid-state battery, comprising the composite solid-state electrolyte membrane as claimed in claim 1 or a composite solid-state electrolyte membrane prepared by the method for preparing the composite solid-state electrolyte membrane as described above.
[0057] The solid-state battery provided by the present invention adopts a polymer matrix with excellent toughness, elasticity and strength as the supporting structure of the diaphragm, and a solid electrolyte membrane is arranged on the surface of the polymer matrix to provide lithium ion conductivity, and the addition of the halide membrane can cooperate with the polymer matrix to make the composite membrane form a dense membrane with low porosity, thereby inhibiting the growth of lithium dendrites, and also facilitating the Li + The rapid transmission of the battery promotes the cycle rate of the battery in a high-temperature environment, so that the formed composite solid electrolyte membrane exhibits the advantages of good toughness, good elasticity, high strength, good thermal stability and high ion conductivity, which can improve the safety and charge and discharge performance of the solid-state battery.
[0058] The lithium iron phosphate composite material provided by the present invention and its preparation method and application are described in detail below in conjunction with specific embodiments.
[0059] Example 1
[0060] The preparation method of the composite solid polymer film provided in this embodiment is as follows:
[0061] Under the protection of argon atmosphere, 33.6 g of acetonitrile, 0.4 g of polyethylene glycol, 0.2 g of lithium bis(trifluoromethylsulfonyl)imide and 0.8 g of polyethylene oxide were weighed and mixed evenly to obtain a slurry with a solid material mass concentration of 4%, wherein the mass ratio of polyethylene glycol to polyethylene oxide was 1:2, and the mass ratio of polyethylene oxide to lithium bis(trifluoromethylsulfonyl)imide was 4:1.
[0062] The slurry obtained above was coated into a film, first dried at room temperature for 8 h under argon conditions, and then transferred to a vacuum environment and further dried at 50° C. for 12 h to obtain a polymer film with a thickness of 5 μm.
[0063] The polymer film and the non-woven fabric coated with Li3ScCl6 were laminated in a manner of polymer film laminated with Li3ScCl6 film laminated with non-woven fabric (compounded with PP / PLA / PE), and the polymer film prepared above and the non-woven fabric coated with Li3ScCl6 were pressed under the conditions of 60°C and 2MPa to obtain a composite solid electrolyte membrane SPE. PEG-PEO-LiTFSI / Li3ScCl6 membrane / non-woven fabric. The non-woven fabric has a thickness of 10 μm, a porosity of 50%, and a Li3ScCl6 membrane thickness of 15 μm.
[0064] Examples 2 to 10, based on Example 1, prepare composite solid electrolyte membranes by adjusting the mass ratio of polyethylene glycol to polyethylene oxide, the mass ratio of bis(fluorosulfonyl)imide lithium salt to polyethylene oxide, and the type of halide membrane.
[0065] In Examples 11-12, a composite solid electrolyte membrane is prepared by adjusting the type of lithium salt based on Example 1.
[0066] Example 13: Based on Example 1, a composite solid electrolyte membrane is prepared by adjusting the type of polymer membrane.
[0067] Example 14: Based on Example 1, a composite solid electrolyte membrane is prepared by adjusting the type of polymer matrix.
[0068] Comparative Example 1
[0069] Except that the slurry does not contain polyethylene glycol, the rest of the contents are the same as in Example 1 to obtain a composite solid electrolyte membrane SPE PEO-LiTFSI / Li3ScCl6 membrane / non-woven fabric.
[0070] Comparative Example 2
[0071] Except that the electrolyte membrane does not contain non-woven fabric, the rest of the contents are the same as in Example 1 to obtain a composite solid electrolyte membrane SPE PEG-PEO-LiTFSI / Li3ScCl6 film.
[0072] Comparative Example 3
[0073] Except that the electrolyte membrane does not contain a halide membrane, the rest of the contents are the same as in Example 1 to obtain a composite solid electrolyte membrane SPE PEG-PEO-LiTFSI / Non-woven fabric.
[0074] Test Case
[0075] The composite solid electrolyte membranes prepared in the above-mentioned Examples 1 to 14 and Comparative Examples 1 to 3 were subjected to impedance analysis tests to obtain the ionic conductivity values of the electrolytes. The specific test process is as follows: After the composite solid electrolyte membrane is pressed into a sheet, it is loaded into a mold sleeve at 60°C, pressurized, and an AC impedance spectrum test is performed using an impedance analyzer, and the ionic conductivity of the electrolyte material is calculated based on the impedance value. The composite solid electrolyte membrane is used as the electrolyte layer of a sulfide all-solid-state metal lithium negative electrode mold battery for charge and discharge tests at 60°C and 0.1C (1C = 180mA / g), and the test results are shown in Table 1.
[0076] Table 1
[0077]
[0078]
[0079] It can be seen from Table 1 that in the embodiment of the present invention, when the mass ratio of PEG:PEO is 1:2, the mass ratio of PEO:Li salt is 4:1, the halide membrane is Li3ScCl6 membrane, and the Li salt is LiTFSI, the prepared composite solid electrolyte membrane SPEPEG-PEO-LiTFSI / Li3ScCl6 membrane / non-woven fabric (composite of PP / PLA / PE) has the highest conductivity, the highest specific capacity at 0.1C charge and discharge for 100 cycles at 60°C, and the retention rate reaches 91%. Combined with comparative examples 1 to 3, it can be compared and analyzed that the introduction of PEG, Li3ScCl6 membrane and non-woven fabric (composite of PP / PLA / PE) can effectively improve the electrochemical properties of the composite solid electrolyte membrane.
[0080] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A composite solid electrolyte membrane, comprising a polymer matrix and a solid electrolyte membrane disposed on the polymer matrix, It is characterized in that The solid electrolyte membrane includes a polymer membrane and a halide membrane which are stacked, and the halide membrane is disposed adjacent to the polymer matrix.
2. The composite solid electrolyte membrane according to claim 1, It is characterized in that The solid electrolyte membrane is disposed on one side or both sides of the polymer matrix.
3. The composite solid electrolyte membrane according to claim 1 or 2, It is characterized in that The raw material composition of the polymer membrane includes polymer electrolyte and lithium salt, and the mass ratio of the polymer electrolyte to the lithium salt is 1 to 20:
1.
4. The composite solid electrolyte membrane according to claim 3, It is characterized in that The mass ratio of the polymer electrolyte to the lithium salt is 1 to 5:
1.
5. The composite solid electrolyte membrane according to claim 3, It is characterized in that The polymer electrolyte is at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinyl alcohol, polycarbonate, polyacrylonitrile, polyvinyl pyrrolidone, polyethylene glycol, polyethylene oxide, and polymethyl methacrylate.
6. The composite solid electrolyte membrane according to claim 5, It is characterized in that The polymer electrolyte is polyethylene glycol and polyethylene oxide in a mass ratio of 1-2:1-3.
7. The composite solid electrolyte membrane according to claim 3, It is characterized in that The lithium salt is at least one of lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium trifluoromethylsulfonyl imide, lithium bis(oxalatoborate), lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium chloride, lithium hexafluorophosphate, and lithium perchlorate.
8. The composite solid electrolyte membrane according to claim 1 or 2, It is characterized in that The polymer film has a thickness of 2 to 50 μm.
9. The composite solid electrolyte membrane according to claim 8, It is characterized in that The thickness of the polymer film is 5 to 30 μm.
10. The composite solid electrolyte membrane according to claim 1 or 2, It is characterized in that The polymer matrix has a porosity of 30-80% and a thickness of 2-40 μm.
11. The composite solid electrolyte membrane according to claim 1 or 2, It is characterized in that The polymer matrix is at least one of non-woven fabric, fiber membrane, melt-blown fabric, and porous diaphragm.
12. The composite solid electrolyte membrane according to claim 1 or 2, It is characterized in that The thickness of the halide film is 5 to 40 μm.
13. The composite solid electrolyte membrane according to claim 1 or 2, It is characterized in that The raw material of the halide film is Li 3 InCl 6 , Li 3 Yb 6 , Li 3 YC 6 , Li 3 ScCl 6 , Li 3 GaCl 6 At least one of .
14. A method for preparing the composite solid electrolyte membrane according to any one of claims 1 to 13, It is characterized in that The steps include: Under a protective atmosphere, a polymer electrolyte, a lithium salt and an organic solvent are mixed to obtain a slurry, the slurry is coated into a film, dried in a protective atmosphere, and then vacuum dried to obtain the polymer film; The polymer film, the raw material of the halide film, and the polymer matrix are stacked and pressed into a film.
15. The method for preparing a composite solid electrolyte membrane according to claim 14, It is characterized in that The mass ratio of the polymer electrolyte to the organic solvent is 1:15-25.
16. The method for preparing a composite solid electrolyte membrane according to claim 15, It is characterized in that The mass ratio of the polymer electrolyte to the organic solvent is 1:15-20.
17. The method for preparing a composite solid electrolyte membrane according to claim 14, It is characterized in that The organic solvent is at least one of methylformamide, acetonitrile, cyclohexanone, heptane, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide.
18. The method for preparing a composite solid electrolyte membrane according to claim 14, It is characterized in that The drying temperature in the protective atmosphere is 20 to 30° C. and the drying time is 2 to 72 hours.
19. The method for preparing a composite solid electrolyte membrane according to claim 18, It is characterized in that The drying time in the protective atmosphere is 4 to 24 hours.
20. The method for preparing a composite solid electrolyte membrane according to claim 14, It is characterized in that The vacuum drying temperature is 30 to 80° C., and the vacuum drying time is 4 to 72 hours.
21. The method for preparing a composite solid electrolyte membrane according to claim 20, It is characterized in that The vacuum drying temperature is 40-60° C., and the vacuum drying time is 12 hours.
22. The method for preparing a composite solid electrolyte membrane according to any one of claims 14 to 21, It is characterized in that The pressing temperature is 30-150° C. and the pressing pressure is 1-10 MPa.
23. A solid-state battery, It is characterized in that The invention comprises the composite solid electrolyte membrane according to any one of claims 1 to 13 or a composite solid electrolyte membrane prepared by the method for preparing a composite solid electrolyte membrane according to any one of claims 14 to 22.
Citation Information
Patent Citations
Composite solid electrolyte membrane, preparation method and lithium-ion battery
CN106654362A
Quasi-solid-state electrolyte film as well as preparation method and application thereof
CN108511791A
Solid electrolyte for lithium metal negative electrode and preparation method thereof
CN110767936A
Organic / inorganic composite porous film and electrochemical device prepared thereby
US20060008700A1
Solid-state hybrid electrolytes, methods of making same, and uses thereof
US20200112050A1
